The unskilled-and-unaware problem and performance feedback in monotonous, easily accustomed, and repetitive work - Yasuhiro Nakamoto; Tomoharu Mori (Scientific Reports)
Abstract The current research examined whether people predict their performance on monotonous, easily accustomed, and repetitive (MEAR) tasks accurately and confirm the effects of performance feedback on their MEAR work predictions. Considering typing on the keyboard as an MEAR task in modern society, 128 university students were asked to type a 12-digit number displayed on each monitor within 5 minutes, explaining that there would be 75 typing problems and participants would receive 20 yen per correct answer. Additionally, participants were informed that they could earn money by reaching a self-determined performance target, with the condition that if they did not reach their self-set goal, they would not receive any earnings. The main findings were as follows: Regardless of the performance levels of typing on keyboards, only 23% of the participants reached the goal, indicating that the absence of performance feedback led to individuals’ overestimation of performance. In contrast, providing feedback significantly improved performance predictions: 76% of the participants reached the goal with feedback on their own performance, 70% with feedback on others’ performance, and 88% with feedback on both their own and others’ performance information. Specifically, the effects between one’s own and others’ performance feedback did not vary at statistically significant levels.